Efficacy of vortioxetine monotherapy compared with combined therapy vortioxetine and olanzapine in the treatment of major depression - first results - Oppa M.; Ondrejka I.; Cesnekova D.; Tonhajzerova I.; Nosalova G. (Sciendo, 2017)
Vortioxetine is a novel antidepressant with two mechanisms of action - direct effect on several serotonin receptors and serotonin reuptake inhibition. Atypical antipsychotics, such as olanzapine, used in the augmentation of antidepressants causes not only a better response to treatment, but also increased number of remissions. The aim of our work was to evaluate the efficacy of vortioxetine monotherapy compared to the combined treatment vortioxetine and olanzapine in adult patients with depression during the acute phase of treatment lasting 6 weeks. Depressive symptomatology was assessed by the MADRS scale, anxiety symptoms were assessed by the HAM-A scale and global clinical impression were evaluated by the CGI-S scale. The number of patients in full-analysis set was 28. The results showed statistically significant improvement in CGI-S for both groups. Patients with vortioxetine monotherapy showed significant improvement in MADRS total score from the third week of treatment (p = 0.009) compared to patients with combined therapy that showed significant improvement since the end of first week of treatment (p = 0.036). Both groups showed significant improvement in HAM-A total score from the second week of treatment. Our results show the possibility of olanzapine in the augmentation strategy in treatment of major depressive disorder in adult patients.